MENGEMBANGKAN MEDIA PEMBELAJARAN ANAK USIA DINI DI PAUD AINUN MAHYA DESA LOBU HUALA KECAMATAN KUALUH SELATAN KABUPATEN LABUHAN BATU UTARA - Susanti, Eka; Nasution, Aida Suciyanti; Syaroh, Aini; Arif, Muhammad Fahrozi; Irwansyah, Rudi (Atthufulah : Jurnal Pendidikan Anak Usia Dini, 2023)
Learning media has already been implemented in schools, and it is necessary to develop learning media in Ainun Mahya PAUD schools. This study aims to determine the development of media in children's education. This study uses a quantitative approach through the use of surveys and quantitative techniques to analyze correlations. In this study, both PAUD students and teachers were used as samples, so that researchers could collect information from primary sources. The research group consisted of PAUD students and teachers. Information-gathering techniques included interviews, observation, and documentation. The subjects from which data could be collected were the focus of this investigation. The fieldwork was carried out in Lobu Huala Village, Kualuh Selatan, Labuhan Batu Utara, Kecamatan. The findings of this study prove emphatically: (1) Limited educational resources at Ainun Mahya PAUD Implementation of Learning Media at Ainun Mahya PAUD Development of Learning Media at Ainun Mahya PAUD, 3. Thus, teachers at PAUD schools in LobuHuala Village, Kualuh Selatan, North Labuhan Batu, need to pay attention to and implement PAUD growth and development through the media.